Correcting the position of piezoelectric transducers during acoustic control of the stressed-strained rolled sections - Tymchik, Gregorii; Filippova, Marina; Demchenko, Mariia (Eastern-European Journal of Enterprise Technologies, 2016)
We used the mirrorshadow method for the diagnostics of stressedstrained state of shaped sections of metal structures. It was found that in the course of implementation of this method there may occur an error that is caused by misalignment of measurement with the dimension of acoustic receiving transducer. The work considers the effect of change in the geometry of shaped sections under the action of maximum permissible stress on the displacement of the point at which a beam of ultrasound wave arrives. We examined a question of influence of the slope of inner edge of the shelf of a shaped section on the displacement of the point of ultrasonic wave’s arrival sideways from the center of receiving transducer. As a result of analytical studies, it was proved that changing geometric dimensions of control object practically does not affect displacement of the point of arrival of the beam from the center of the receiving transducer. It was found that for a number of shaped sections that have slopes of internal edges of the shelves, it is necessary to introduce correction of position of the receiving transducer relative to the emitting transducer by such parameters as angle and distance relative to the anchor point. Performed research is a prerequisite for the development of design of the block of piezoelectric transducers for implementation of the system of acoustic diagnostics of the strained state of shaped sections.